2001
DOI: 10.3354/ame025103
|View full text |Cite
|
Sign up to set email alerts
|

Functional similarity of attached and free-living bacteria during freshwater phytoplankton blooms

Abstract: Phytoplankton blooms were created in freshwater enclosures to study the functional succession and diversification for attached (>10 µm size fraction) and free-living (<10 µm size fraction) assemblages of bacteria. Bacterial dynamics in abundance, production and enzyme activity was monitored by standard methods. The functional diversity with respect to sole carbon source utilization was assessed with Biolog GN plates inoculated with bacteria from the 2 size fractions. Moreover, bacterial isolates were screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 53 publications
6
22
0
Order By: Relevance
“…Comparison of microscopic observations before and after sonication showed that our sonication procedure on 0.8 µm filters do not damage the cells and resulted in >95% recovery of particle-attached bacterial cells. In addition, 44 samples analyzed by both methods showed no significant differences (mean=5.9±1.8 and 6.8±1.3×10 5 cells ml −1 by epifluorescence and flow cytometry, respectively) and were closely correlated (R=+0.68, p<0.01, n=44) that confirmed the validity of using sonication before flow cytometric enumerations as shown previously (Riemann and Winding, 2001;Worm et al, 2001).…”
Section: Study Site and Samplingssupporting
confidence: 65%
“…Comparison of microscopic observations before and after sonication showed that our sonication procedure on 0.8 µm filters do not damage the cells and resulted in >95% recovery of particle-attached bacterial cells. In addition, 44 samples analyzed by both methods showed no significant differences (mean=5.9±1.8 and 6.8±1.3×10 5 cells ml −1 by epifluorescence and flow cytometry, respectively) and were closely correlated (R=+0.68, p<0.01, n=44) that confirmed the validity of using sonication before flow cytometric enumerations as shown previously (Riemann and Winding, 2001;Worm et al, 2001).…”
Section: Study Site and Samplingssupporting
confidence: 65%
“…However, based on the results, it was observed that arabinosidase, fucosidase and rhamnosidase presented lower activity in the attached form than in the free-living form, and free enzymes revealed an important proportion (38-55 %) compared to the former (Table 2). Glucosidases (α-and β-) reached values comparable to other freshwater studies (Worm et al, 2001;Lemarchand et al, 2006). Working with fractionated samples Richardot et al (1999) registered the highest enzymatic activities for glucosidases (α-and β-) in the attached fraction (2-100 µm).…”
Section: Resultssupporting
confidence: 80%
“…Conventionally, bacteria associated to marine snow and particulate matter express more enzymatic activities than the surrounding water mainly during phytoplanktonic blooms (Worm et al, 2001). Taking into account the high extracellular enzymatic activity of associated bacteria when compared to free-living bacteria, it may be assumed that this activity would degrade high molecular organic compounds of the aggregate, which would compromise the maintenance of the structure of the aggregates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have documented the correlation between phytoplankton and bacterial community dynamics, particularly at weekly or more frequent timescales (Worm et al 2001;Kent et al 2004;Newton et al 2006). In our data set, no relationship was found between phytoplankton community composition and BCC at the biweekly timescale (data not shown).…”
Section: Discussionmentioning
confidence: 99%